The textural properties of cooked convenience rice upon repeated freeze–thaw treatments are largely affected by water mobility at grain level. (January 2023) - Lu, Shiyi; Li, Jie; Xu, Minghao; Mu, Yifan; Wen, Yangyang; Li, Hongyan; Wang, Jing; Sun, Baoguo
Graphical abstract: Highlights: Repeated freeze–thaw treatment induced reductions in rice hardness and stickiness. Rice hardness tend to be negatively related to the pore size of starch matrix. Ultrasound-assisted cellulase treatment retarded starch retrogradation. All convenience rice texture was largely influenced by water mobility. Abstract: Brown rice (BR) is a promising source for convenience rice that are mostly stored frozen. However, freezing and thawing may cause deterioration in rice texture quality. To investigate how rice texture is influenced by freeze–thaw cycles, BR, the pretreated BR with partially ruptured bran layer (UER) and white rice (WR) were cooked and treated with repeated freeze–thaw cycles, with their textural properties, variations in moisture distribution and starch structure being measured. Results showed that the repeated freeze–thaw treatment induced a progressive reduction in hardness and stickiness of all cooked rice. The reduced hardness of rice could be explained by the enlarged pore size of starch inside rice under scanning electron microscopy. Moisture migration in WR was the fastest responding to multiply freeze–thaw cycles, followed by UER, while water mobility in BR was slowest. Moreover, WR, BR and UER resulted in a similar extent of amylopectin retrogradation and chains length distribution after repeated freeze–thaw cycles. It indicated similar and minor effect of starch variations on determining the texture of different rice samples against freeze-thawing. Water mobility tended to be a main factor leading to the textural difference of fully gelatinized rice samples. This study focused on the relationship between water distribution and starch retrogradation, providing a better understanding on influences of multiple freeze-thawing on textural quality of cooked rice maintaining different extents of surface layer.